Standardization of Alternative Learning Modality in the Higher Education Institution (HEIS) In Albay - Betiz, Jeymar (JPAIR Multidisciplinary Research, 2022)
Standardizing alternative learning modalities in private and public schools encountered problems among Higher Education Institutions (HEIs) in Albay. Poor internet connectivity and lack of trainings for faculties and students is the most massive problem upon implementing the alternative learning modality with limited face-to-face classes. The study gives an important guide and information to the Commission on Higher Education (CHED) and the Higher Education Institutions (HEIs) in Albay in implementing standardization of alternative learning modalities with or without the pandemic. To accomplish the objectives of the research, the mixed method is used a descriptive qualitative method and a descriptive-quantitative method. The primary sources of data were the school administrators’ Higher Education Institutions in the first district, second district, and third district province of Albay. To create and implement an effective standardization of alternative learning modality among Higher Education Institutions (HEIs) in the province of Albay, a proposed model called BETIZ model is projected. It represents the processes to Build, Evaluate, Test, Implement, and Zeal for Excellence in making operations of alternative learning modality successful that can be adopted by the target beneficiary of the study.